Swallow safety is determined by bolus volume during infant feeding in an animal model - Mayerl, Christopher J (Dysphagia, 2020)
Feeding difficulties are especially prevalent in preterm infants, although the mechanisms driving these difficulties are poorly understood due to a lack of data on healthy infants. One potential mechanism of dysphagia in adults is correlated with bolus volume. Yet, whether and how bolus volume impacts swallow safety in infant feeding is unknown. A further complication for safe infant swallowing is recurrent laryngeal nerve (RLN) injury due to patent ductus arteriosus surgery, which exacerbates the issues that preterm infants face and can increase the risk of dysphagia. Here, we used a validated animal model feeding freely to test the effect of preterm birth, postnatal maturation and RLN lesion and their interactions on swallow safety. We also tested whether bolus size differed with lesion or birth status, and the relationship between bolus size and swallow safety. We found very little effect of lesion on swallow safety, and preterm infants did not experience more penetration or aspiration than term infants. However, term infants swallowed larger boluses than preterm infants, even after correcting for body size. Bolus size was the primary predictor of penetration or aspiration, with larger boluses being more likely to result in greater degrees of dysphagia irrespective of age or lesion status. These results highlight that penetration and aspiration are likely normal occurrences in infant feeding. Further, when comorbidities, such as RLN lesion or preterm birth are present, limiting bolus size may be an effective means to reduce incidences of penetration and aspiration.